P16 expression and recurrent cervical intraepithelial neoplasia after cryotherapy among women living with HIV - Maina, Daniel; Chung, Michael H.; Temmerman, Marleen; Moloo, Zahir; Wawire, Jonathan; Greene, Sharon A.; Unger, Elizabeth R.; Mugo, Nelly; Sakr, Samah; Sayed, Shahin; McGrath, Christine J. (Frontiers in Medicine, 2023)
The expression of p16 protein, a surrogate marker for high-risk human papillomavirus (hrHPV), is associated with cervical dysplasia. We evaluated correlates of p16 expression at treatment for high-grade cervical lesions and its utility in predicting the recurrence of cervical intraepithelial lesions grade 2 or higher (CIN2+) following cryotherapy among women with HIV.Methods: This is a subgroup analysis of women with HIV in Kenya with baseline cervical biopsyconfirmed CIN2+ who were randomized to receive cryotherapy and followed every six-months for twoyears for biopsy-confirmed recurrence of CIN2+. P16 immunohistochemistry was performed on the baseline cervical biopsy with a positive result defined as strong abnormal nuclear expression in a continuous block segment of cells (at least 10-20 cells). Results: Among the 200 women with CIN2+ randomized to cryotherapy, 160 (80%) had a baseline cervical biopsy specimen available, of whom 94 (59%) were p16-positive. p16 expression at baseline was associated with presence of any one of fourteen hrHPV genotypes [Odds Ratio (OR)=3.2; 95% Confidence Interval (CI), 1.03-9.78], multiple lifetime sexual partners (OR=1.6; 95% CI, 1.03-2.54) and detectable plasma HIV viral load (>1,000 copies/ml) (OR=1.43; 95% CI, 1.01-2.03). Longer antiretroviral therapy duration (≥2 years) at baseline had lower odds of p16 expression (OR=0.46; 95% CI, 0.24-0.87) than <2 years of antiretroviral therapy. Fifty-one women had CIN2+ recurrence over two-years, of whom 33 (65%) were p16-positive at baseline. p16 was not associated with CIN2+ recurrence (Hazard Ratio=1.35; 95% CI,.In this population of women with HIV and CIN2+, 41% of lesions were p16 negative and baseline p16 expression did not predict recurrence of cervical neoplasia during two-year follow up.